Nestin expression in high-grade osteosarcomas and its clinical significance - Zambo, Iva; Hermanova, Marketa; Adamkova Krakorova, Dagmar; Mudry, Peter; Zitterbart, Karel; Kyr, Michal; Vesely, Karel; Sterba, Jaroslav; Veselska, Renata (Oncology reports, 2012)
Nestin has been detected in various malignancies and its expression correlates with advanced grade in some neoplasms. The aim of this study was to examine nestin expression in high-grade osteosarcomas and to determine its prognostic value. Using immunohistochemistry and immunofluorescence, we evaluated nestin expression in tumor tissue samples from 45 patients with high-grade osteosarcomas. In both methods, the frequency of nestin-positive tumor cells was classified into three categories (1+, 2+ and 3+ for immunohistochemistry; 1F+, 2F+ and 3F+ for immunofluorescence) and clinicopathological correlations were statistically evaluated and analyzed. Nestin-positive tumor cells were detected in all of the examined osteosarcomas using both immunohistochemistry and immunofluorescence, although the proportion of undoubtedly positive neoplastic cells varied in individual samples from a few nestin-positive tumor cells to diffuse nestin positivity. High levels of nestin expression detected by immunofluorescence (2F+ and 3F+) were associated with worse clinical outcomes (OS, p=0.031; EFS, p<0.001). However, high levels of nestin expression as measured by immunohistochemistry trended towards shorter patient survival rates but did not reach statistical significance. Despite significantly shorter survival rates observed in patients with high levels of nestin expression assessed by immunofluorescence, nestin does not seem to represent a powerful prognostic marker that would be superior to conventional methods.
Keywords: Young Adult; nádory kostí; Male; osteosarkom; Nerve Tissue Proteins; Bone Neoplasms; mladý dospělý; Neoplasm Grading; Adolescent; prognóza; Child; Nestin; proteiny nervové tkáně; dítě; Adult; Osteosarcoma; Aged; dospělí; mužské pohlaví; senioři; mladiství; senioři nad 80 let; lidé; ženské pohlaví; Intermediate Filament Proteins; stupeň nádoru; Humans; proteiny intermediálních filament; Aged, 80 and over; Prognosis; Female; lidé středního věku; nestin; Middle Aged